Effects of Intact Carcass Electrical Stimulation on Moisture Retention Characteristics of Polyphosphate-Treated Non-Aged Boneless Broiler Breast Fillets - Young, L.L.; Smith, D.P.; Cason, J.A.; Walker, J.M. (International Journal of Poultry Science, 2004)
The objective of this study was to evaluate combined effects of whole carcass electrical stimulation and polyphosphates on moisture absorption and retention by marinated non-aged boneless chicken breast fillets. Breast fillets were harvested from electrically stimulated and non-stimulated carcasses immediately after chilling. Half were immediately marinated in saline solution and half in a similar solution containing sodium tripolyphosphate. Muscle pH before and after marination, marinade absorption and cooking loss were recorded. Electrical stimulation immediately depressed muscle pH, but polyphosphate marination mitigated that trend somewhat. Electrical stimulation improved marinade absorption (10.6±0.3% verses 8.8±0.3%) but did not affect cooking loss. Polyphosphates did not affect marinade absorption, but significantly reduced cooking losses (17.3±0.4% verses 14.1±0.4%). No marinade by electrical treatment interactions affecting moisture absorption or retention by the fillets were detected.